Comparison of postpartum family planning uptake between primiparous and multiparous women in Webuye County Hospital, Kenya - Henry O. Owuor (South African Family Practice)
Background: Postpartum family planning (PPFP) is associated with health, social and economic benefits to a woman and her family. Its uptake, particularly of the more effective, long-acting reversible contraceptives (LARCs), is low. The role of parity in PPFP uptake is inconclusive. The aim of this study was to compare the uptake of PPFP and LARCs between primiparous and multiparous women accompanying their children for the first measles vaccine, which is at 9 months after delivery, in Webuye County Hospital, Kenya.